Peningkatan Efektivitas Produksi Dan Perluasan Pasar Terasi Udang Di KB Khinasih Dengan Alat Pengering Terasi Dan Rebranding Produk - Aprillia, Happy; Jaya, Asma; Waskito, Indra Budi; Hudayana, Nurul; Ananda, Ryan; Iqbal, Muhammad; Yuserby, Muhammad; Ondi, Daniel; Natanael, Sergius (STMIK Royal, 2024)
This community service (PkM) was conducted near the coast of Manggar Beach, Balikpapan City, in collaboration with partners from the PKK Khinasih Quality Family Village (KB Khinasih) group, which has micro-industry potential for processed shrimp paste. The challenges faced include: 1) the drying method for shrimp paste is conducted by sun-drying, which means that during the rainy season, the drying process for shrimp paste takes a long time and hampers the production process; and 2) sales of processed shrimp paste products are currently limited to the local community. To address these issues related to the extended drying process and to expand marketing efforts, this PkM initiative developed a shrimp paste drying tool tailored to the needs of the PKK KB Khinasih women. Additionally, outreach activities were conducted to educate them about design and packaging strategies that could be beneficial for hosting product exhibitions. The dryer has been handed over to the PKK women for suitability testing with regard to its function, quality, and capacity. KB Khinasih has also adopted label and sticker designs for packaging processed rebon shrimp paste products. Keywords: dryer; product sticker and label; rebon shrimp paste